PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN PRODUKTIVITAS KERJA PADA PT. KUNANGO JANTAN KABUPATEN KAMPAR - ,Marzolina, Damai Sara , Hj. Sri Indarti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of motivation and job satisfaction on organizational commitment and work productivity at PT. Kunango Jantan, Kampar district. This study used primary data in the form of a questionnaire with processing using SPSS 23. The population in this study were 129 people with a sample of 97 people. Methods of data analysis using path analysis. The results of the study indicate that there is a positive and significant influence between motivation and job satisfaction on organizational commitment. Motivation and job satisfaction have a positive and significant effect on work productivity. Organizational commitment has a positive and significant effect on work productivity. There is an influence between motivation on work productivity through organizational commitment. There is an influence between job satisfaction on work productivity through organizational commitment. Keywords: Motivation, job satisfaction, organizational commitment, and work productivity.